2020
DOI: 10.1039/d0na00268b
|View full text |Cite
|
Sign up to set email alerts
|

New volumetric CNT-doped gelatin–cellulose scaffolds for skeletal muscle tissue engineering

Abstract: Currently, the fabrication of scaffolds for engineered skeletal muscle tissues is unable to reach the millimeter size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 69 publications
0
19
0
Order By: Relevance
“…Several studies conclude that electrical stimulation and mechanical tension favor the maturation of the tissues. 35 , 61 , 79 Current studies to develop human functional bioartificial muscle use fibrin-based hydrogels. Fibrin composite matrices have tunable mechanical properties, can be remodeled by cells, and allow long-term cultures.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies conclude that electrical stimulation and mechanical tension favor the maturation of the tissues. 35 , 61 , 79 Current studies to develop human functional bioartificial muscle use fibrin-based hydrogels. Fibrin composite matrices have tunable mechanical properties, can be remodeled by cells, and allow long-term cultures.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, anisotropic gelatin-cellulose cryogels were generated to engineer volumetric skeletal muscle using C2C12 myoblasts. 61 Anisotropic cryogels improve cell alignment, myotube fusion, and myogenic maturation ( Figure 4(c) ). Moreover, the addition of carbon nanotubes (CNTs) to the cryogel improves the electrical properties of the scaffolds, which enhances early myogenic maturation steps when electric pulse stimulation is applied.…”
Section: D Engineering For Skeletal Muscle Culturementioning
confidence: 99%
See 2 more Smart Citations
“…They reported that GO-implemented aligned nanofibers did not exhibit the same cell orientation as the cells in contact with pure PCL-aligned nanofibers. Carbon nanotubes (CNTs) have been investigated for the formulation of scaffolds for the potential application of skeletal muscle regeneration [ 181 ]. Patel et al built CNT-based hierarchical scaffolds in two different forms, interconnected microporous foams or aligned fiber mats, with tunable physicochemical behavior.…”
Section: Biomaterials For the Transplantation Of Striated Muscle Cellsmentioning
confidence: 99%